How We Got into Drum Circles, and How to Get Out: De-Essentializing African Music - Carter-Ényì, Quintina; Carter-Ényì, Aaron; Hylton, Kevin (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2019)
Babatunde Ọlátúnjí’s Drums of Passion (1960) caught the attention of prominent American musicians from John Coltrane to the Grateful Dead and turned on subsequent generations to West African djembe drumming. The inclusion of djembe drum circles in education is alarming because they are “based on the partial appropriation and transformation” of African-based drumming. This article suggests how to get out of drum circles by recognizing and embracing African melody, especially pitched idiophones and ensemble singing. We describe a program at two Historically Black Colleges that combines more equitable and accurate representation of African cultures with technological literacy and a greater range of learning modalities.